Determinism and judgment : a critique of the indirect epistemic transcendental argument for freedom - Zanetti, Luca (Array, 2019)
In a recent book entitled Free Will and Epistemology. A Defence of the Transcendental Argument for Freedom, Robert Lockie argues that the belief in determinism is self-defeating. Lockie’s argument hinges on the contention that we are bound to assess whether our beliefs are justified by relying on an internalist deontological conception of justification. However, the determinist denies the existence of the free will that is required in order to form justified beliefs according to such deontological conception of justification. As a result, by the determinist’s own lights, the very belief in determinism cannot count as justified. On this ground Lockie argues that we are bound to act and believe on the presupposition that we are free. In this paper I discuss and reject Lockie’s transcendental argument for freedom. Lockie’s argument relies on the assumption that in judging that determinism is true the determinist is committed to take it that there are epistemic obligations – e.g., the obligation to believe that determinism is true, or the obligation to aim to believe the truth about determinism. I argue that this assumption rests on a wrong conception of the interplay between judgments and commitments.